9(j-4)=8

Simple and best practice solution for 9(j-4)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(j-4)=8 equation:


Simplifying
9(j + -4) = 8

Reorder the terms:
9(-4 + j) = 8
(-4 * 9 + j * 9) = 8
(-36 + 9j) = 8

Solving
-36 + 9j = 8

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 9j = 8 + 36

Combine like terms: -36 + 36 = 0
0 + 9j = 8 + 36
9j = 8 + 36

Combine like terms: 8 + 36 = 44
9j = 44

Divide each side by '9'.
j = 4.888888889

Simplifying
j = 4.888888889

See similar equations:

| -9x+3(5)=-3 | | 9x-(2x+3)=8x-40 | | 0.9x-4.6=0.8 | | 3=(12-3a)/6 | | brian+kevin= | | 4/5b=12 | | 5(54+y)=15y | | 7(5)=-40+x | | 4+4x-3x=7 | | 8y+2(y-6)=5(y+1)-3 | | 82x^2-5x+674=0 | | -6(x+7)=-31 | | 3(4+3x)=8(x-1) | | 3y=15x-3 | | 5/9(g+18)=16g+3 | | -4(2x-6x)+8x=5x+24+x | | 57=6x+5x-9 | | 9+8n=4n+9 | | -32-7n=n+7(7-5n) | | m+m+m+m+m= | | x+3(1-x)=9 | | X/2+3=7/2 | | -3x+32-7x=-2(5x+10) | | x+(x+1)+(x+2)+(x+3)+(x+4)+(x+5)+(x+6)+(x+7)+(x+8)+(x+9)=145845 | | x+3(-5x)=-28 | | 3x-(-5x-7)=-9 | | x-(5-3x)=7x | | x+5x+2x= | | (7x-5)=44 | | 12n+8b=48 | | 35-10x+3=20 | | (7x-5)+44= |

Equations solver categories